2020
DOI: 10.1021/acsnano.0c02885
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Engineering of Morphology and Electronic Band Gap in Lateral Heterostructures of Monolayer Transition Metal Dichalcogenides

Abstract: Heterostructures of two-dimensional transition metal dichalcogenides (TMDs) can offer a plethora of opportunities in condensed matter physics, materials science, and device engineering. However, despite state-of-the-art demonstrations, most current methods lack enough degrees of freedom for the synthesis of heterostructures with engineerable properties. Here, we demonstrate that combining a postgrowth chalcogen-swapping procedure with the standard lithography enables the realization of lateral TMD heterostruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Transition metal dichalcogenides (TMDs) have attracted tremendous research interest due to their extraordinary physical their natural features of band structures, chemical instability, and difficulties in synthesis. To fulfill the demand for diverse types of band alignments, band gap engineering, perhaps the most likely path, including modifications by external forces like mechanical force, [12][13][14] electric field, [15] magnetic field, [16] and material modifications like interface engineering, [17] defect engineering, [18] doping, [19] alloying, [20,21] and so on. To date, considerable work was reported to modify the energy band structures of TMDs heterostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal dichalcogenides (TMDs) have attracted tremendous research interest due to their extraordinary physical their natural features of band structures, chemical instability, and difficulties in synthesis. To fulfill the demand for diverse types of band alignments, band gap engineering, perhaps the most likely path, including modifications by external forces like mechanical force, [12][13][14] electric field, [15] magnetic field, [16] and material modifications like interface engineering, [17] defect engineering, [18] doping, [19] alloying, [20,21] and so on. To date, considerable work was reported to modify the energy band structures of TMDs heterostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, a variety of 2D lateral TMD-HSs have been synthesized. 10,25,26,38,46,53,[56][57][58][59][60] Duan et al have reported the growth of MoS 2 -MoSe 2 and WS 2 -WSe 2 lateral HSs by chemical vapor deposition (CVD), 25 and later they reported the endoepitaxial growth of monolayer mosaic HSs by laser patterning and an anisotropic thermal etching process to create triangular hole arrays in 2D crystals, followed by endoepitaxial growth of another 2D crystal. The resulting mosaic in-plane HS arrays (such as WS 2 -WSe 2 , WS 2 -MoS 2 , and WSe 2 -MoS 2 ) show atomically sharp heterojunction interfaces and systematically tunable modulation of chemical compositions and lattice strains.…”
Section: Introductionmentioning
confidence: 99%
“…61 Interestingly, MoS 2x Se 2(1−x) -MoS 2y Se (1−y) exhibits a wide bandgap tunability of 0.32 eV. 53,59 These synthesized 2D lateral TMD-HSs have been assembled into devices for electronic and optoelectronic applications such as lateral p-n diodes, 46,56 photodiodes, 42 photodetectors, 62 high-repetition excitonic devices 63 and fieldeffect transistors (FETs). 9 Meanwhile, the theoretical studies of lateral TMD-HSs were mainly focused on the electronic band structures and band offsets.…”
Section: Introductionmentioning
confidence: 99%
“…The epitaxial growth of 2D heterostructures mostly depends on the random nucleation, which limits the controllability and homogeneity of the crystal size and location. In order to fabricate periodically patterned heterostructures, block copolymer lithography and e-beam lithography were introduced before or after growth. However, the lithography processing and the involved solution treatment inevitably contaminate the ultrathin materials by introducing residues, which deteriorates the device performance.…”
Section: Introductionmentioning
confidence: 99%